Affirmative Action and Political Dispute in Today's Brazilian Academe. (September 2014) - dos Santos, Sales Augusto
The current discussion about the quota system being introduced to increase access by black students to public universities in Brazil has at least two components. The first is who can acquire one of the prerequisites to entering Brazil's ruling establishment: a degree from a Brazilian public university. The second is what paradigm for interpreting race relations is most pertinent to the real situation in Brazil. Neste artigo discute-se o que está sob disputa na sociedade brasileira com a implementação do sistema de cotas para estudantes negros ingressarem nas universidades públicas b rasileiras. Levanta-se a hipótese de que há pelo menos duas disputas. A primeira é sobre quem poderá adquirir um dos pré-requisitos para aspirar fazer parte das elites dirigentes deste país: o diploma de uma universidade pública brasileira. A segunda disputa é sobre qual paradigma de interpretação das relações raciais é mais pertinente para a realidade brasileira.